Photoinduced chitosan–PEG hydrogels with long-term antibacterial properties. Issue 42 (3rd October 2019) - Sautrot-Ba, P.; Razza, N.; Breloy, L.; Andaloussi, S. Abbad; Chiappone, A.; Sangermano, M.; Hélary, C.; Belbekhouche, S.; Coradin, T.; Versace, D.-L.
Abstract : The photo-induced synthesis of chitosan–PEG hydrogels with tremendous antibacterial and anti-adhesive properties even after 6 months' storage. Abstract : Photochemical processes offer the possibility of preparing functional hydrogels under green conditions that are compatible with both synthetic and natural polymers. In this study, chitosan-based poly(ethylene) glycol (PEG) were successfully synthesized under light irradiation in aqueous medium. Kinetic studies under irradiation showed that less than 2 min were necessary to obtain fully cross-linked networks. Thermomechanical analyses and swelling experiments indicated that introduction of chitosan overall weakens the hydrogel network but can create domains of higher thermal stability than the PEG-alone structure. The resulting chitosan–PEG hydrogels demonstrated a tremendous inhibition (100%) of bacterial growth ( Escherichia coli and Staphylococcus aureus ). After 6 months' ageing, one of the hydrogels preserved a high antifouling activity against Escherichia coli . This interesting result, which could be correlated with the network features, demonstrates the strong potential of these photochemical methods to obtain robust bio-functional materials.